EFEKTIVITAS DAN EFISIENSI PENERAPAN SISTEM ANTRIAN BERBASIS ONLINE (SPEEDID) DALAM MENGOPTIMALKAN KUALITAS PELAYANAN DI MASA PANDEMI COVID-19 PADA PT BANK BPD BALI CABANG KLUNGKUNG - Tjokorda Rania Pratami; Nyoman Indah Kusuma Dewi; Cokorda Gede Putra Yudistira (Jurnal Bisnis dan Kewirausahaan, 2022)
This research aims to analyze the extent of effectiveness and efficiency of applications of Online-Based Queuing System (SpeedID) in optimizing the services quality during the pandemic Covid-19 at Bank BPD Bali Klungkung Branch. This research uses a qualitative descriptive method with a case study approach. Data collection is done by using observation, interview and documentation techniques. Interview informants include internal (staff) and external (customers) Bank BPD Bali Klungkung Branch. Data analysis was carried out with the stages of data reduction, data display, and drawing conclusions using pattern matching techniques. Research results indicate that effectiveness and efficiency of applications of Online-Based Queuing System (SpeedID) in optimizing the service quality during pandemic Covid-19 at Bank BPD Bali Klungkung Branch which is not maximized. It is caused by the disturbance of the program and the goal achievements caused by various obstacles like systems or tissue distractions, still many customers of manual queues, an often over looked time estimate. With these obstacles, it causes optimalization of customer time and ease access service through the Online-Based Queuing System (SpeedID) has not been fully sensed. In addition, improvements are needed from the service side, such as increasing the ability and work discipline in the Teller Unit, as well as reviewing infrastructure procurement and spatial planning, especially in the outdoor waiting room and customer parking.